Optimalisasi Pembelajaran Al-Qur’an dengan Media Flash Card di Masjid Nur Hasan, Padukuhan Pakel Jaluk, Kalurahan Piyaman, Kabupaten Gunungkidul - Muhammad Rifki Rizqullah; Sheindy Wanurvikhi Dianatta; Angger Bimantara (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2025)
In this study, we address the use of flash cards as a medium for Qur'anic reading instruction in mosques. This exercise was selected because it is crucial for Muslims to comprehend and become proficient in reciting the Qur'an in their daily lives. Participants are actively involved in the learning process because to the interactive approach used in this session. The training's outcomes show that participants' reading skills of the Qur'an have significantly improved, and their desire to study more has grown. Nevertheless, this training has a number of drawbacks, such as the short amount of time allotted for each session, which might not be enough for a thorough examination of the subject matter. Furthermore, different participants have varying backgrounds in Qur'anic reading, which makes it difficult to adapt teaching strategies to suit each student's needs. In conclusion, even if using flash cards has been shown to improve Qur'anic reading skills, more focus must be placed on time management and method modifications to attain the best possible outcomes. It is anticipated that other communities will embrace this exercise more frequently in order to improve religious understanding.